Pengaruh Teknologi, Inovasi, dan Entrepreneurs Terhadap Perkembangan Wilayah Daerah Istimewa Yogyakarta - Rian Marita Sugiarto; Doddy Aditya Iskandar (REKA RUANG, 2022)
Every region is characterized by the diversity of natural resources and demographic structure. It causes every region may have different comparative advantages. A region could utilize technology if it has limitations on natural resources. This research, therefore, aims to investigate the role of technology development in enhancing regional development in the Yogyakarta Special Region. This research uses three macro indicators, which are economic growth rate, human development index, and poverty index to measure regional development. Data panel is obtained from 4 regencies and 1 municipality in Yogyakarta from 2014 until 2018. The dataset is then analyzed using Structural Equation Modelling in SmartPLS software. GIS Software is also utilized to depict the spatial effect from the dataset modeling. The analysis result shows that Sleman Regency and Yogyakarta Municipality are regions with a high concentration of technology. Bantul Regency, which is adjacent to those two aforementioned regions, is coming behind regarding the concentration of technology. Meanwhile, Kulon Progo and Gunungkidul Regency are deemed as lagging behind those three Regions in Yogyakarta Special Region in terms of technology concentration. However, as shown by this research, technology development and highly educated human resource would not enhance regional development if it is not in line with the demand for technology from the industrial sector within a region.